2014
DOI: 10.1097/opx.0000000000000232
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of Antimicrobial Melimine Lenses

Abstract: Melimine-coated contact lenses were worn safely by humans. However, they were associated with higher corneal staining. The melimine-coated lenses retained high antibacterial activity after wear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 53 publications
3
54
0
Order By: Relevance
“…In vivo melimine coatings demonstrated a significant reduction of CLPU incidence in the rabbit model [19]. The broad-spectrum antimicrobial activity of melimine was also confirmed in a human clinical trial, where melimine-coated lenses turned out to be safe for use during wear and retained a high antimicrobial activity after wear [20]. Other studies have shown that the melimine coating was heat-stable, non-toxic to mammalian cells in vitro, and did not alter the physical dimensions of CL [17,19,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo melimine coatings demonstrated a significant reduction of CLPU incidence in the rabbit model [19]. The broad-spectrum antimicrobial activity of melimine was also confirmed in a human clinical trial, where melimine-coated lenses turned out to be safe for use during wear and retained a high antimicrobial activity after wear [20]. Other studies have shown that the melimine coating was heat-stable, non-toxic to mammalian cells in vitro, and did not alter the physical dimensions of CL [17,19,21].…”
Section: Discussionmentioning
confidence: 99%
“…Direct topical AMPs application, production of AMP’s derivatives and peptidomimetics, construction of specifically-targeted AMPs (STAMP), or immobilization of AMPs directly onto the surface of biomaterials are some of the examples [16,17]. Several in vitro and in vivo studies have been performed to investigate a group of AMPs as potential anti-biofilm agents for ocular infection therapies [17,18,19,20,21]. …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, implants and other medical devices can also reduce bacterial colonization, biofilm formation, and infection rates, presenting long lasting functionality, broad-spectrum activity, and minimal cytotoxicity against human cells. 276,277 Human AMPs could, theoretically, also be used as biosensors immobilized onto microchips for identification purposes, allowing the identification of microorganisms. However, such applications have only been exploited with animal or synthetic AMPs.…”
Section: Application Of Amps Beyond Conventional Pharmacological Therapymentioning
confidence: 99%
“…Risk factors for microbial keratitis include: ( i ) extended wear of CL; ( ii ) CL wear while swimming; ( iii ) improper storage and disinfection of lenses with tap water or home‐made solutions; ( iv ) wear of cosmetic CL, especially if purchased online or from roadside shops . Importantly, newer lens materials, care regimes, and wear modalities have not reduced the incidence and severity of infections .…”
Section: Introductionmentioning
confidence: 99%